Measurement of rivulet movement on inclined cables during rain–wind induced vibration - Li, Yongle; Jing, Haiquan; Xia, Yong; Xu, Youlin; Xiang, Huoyue (Sensors and actuators. A. Physical., 2015)
•We developed an image processing method to measure the position of rivulets.•This method does not affect the rivulet formation and wind flow field.•For the first time, the rivulet along the entire cable is measured.•The averaged upper rivulet oscillates almost in-phase with the cable vibration. The large amplitude vibration of stay cables has been observed in several cable-stayed bridges under the simultaneous occurrence of rain and wind, which is called rain–wind induced vibration (RWIV). During RWIV, the upper rivulet oscillating circumferentially on the inclined cable surface is widely considered to have an important role in this phenomenon. However, the small size of rivulets and high sensitivity to wind flow make the measurement of the rivulet movement challenging. This study proposes a digital image processing method to measure the rivulet movement in wind tunnel tests. RWIV of a cable model was excited during the test and a digital video camera was used to record the video clips of the rivulets, from which the time history of the rivulet movement along the entire cable is identified through image processing. The oscillation amplitude, equilibrium position, and dominant frequency of the upper rivulet are investigated. Results demonstrated that the proposed non-contact, non-intrusive measurement method is cost-effective and has good resolution in measuring the rivulet vibration. Finally the rivulet vibration characteristics were also studied when the cable was fixed. Comparison demonstrates the relation between the upper rivulet and cable vibration.